The Element of Archetypes that Focused on The Character of The Film Encanto (2021) - Ani Widiyanti; Sthela Oktavia Husen; Ardetia Lara Zesika (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
This study aims that cartoon films can also be analyzed by psychoanalysis, through the archetype theory approach from Carl Jung. archetypes are the means given some of the experiences and memories of our ancestors. This way is part of the collective unconscious. The characteristics of the archetypes that are generated due to sociocultural influences. This means that each individual cannot develop archetypes according to their own experiences, but also stems from their social and environmental existence. The author discusses this story using descriptive qualitative methods to discuss the problems that exist in the story. The author analyzes by watching, analyzing, then recording the results of the analysis in this journal. From this research, the writer finds several types of archetypes in the characters in the film, those archetypes are Animus, Persona, Hero, Great Mother, Wild Old Man, and Shadow. The author can find out about this through the character played by the Madrigal family.Keywords: archetype; character; encanto.